(untitled) (Research, Society and Development, 2019)
Globalization is a current and necessary topic for the debate with students of Basic Education. In addition, it integrates the curricular components of Geography in the Final Years of Elementary School, especially in the 8th and 9th years. Based on this, the present article aimed to report on a review activity on the content of globalization that was developed with a 9th grade class of Elementary School, EMEF Junto ao CAIC Luizinho de Grandi, Santa Maria/RS, in February 2019. This activity involved critical reflective debates and used different didactic resources, thus enhancing the student’s argument on the subject and leading them to a more consistent interpretation of what is and the consequences and potential of globalization. It was concluded that the didactic sequence proved to be effective and contributed to dynamize the pedagogical space of the classroom by stimulating the student’s critical thinking and their positioning in the current context of the global world.